The Influence of Dividend Policy, ESG Score, Profitability, and Leverage on the Stock Liquidity of IDX 80 Companies on the Indonesia Stock Exchange - Arista Palupi; Febria Nalurita; Hamdy Hady (Eduvest - Journal of Universal Studies, 2024)
This study aims to analyze the effect of dividend policy measured with DPR, envirometal, social, governance (ESG score), profitability measured by ROA and leverage measured by DER toward stock liquidity by using amihud methods at 80 IDX companies registered in IDX period 2018-2022. This study sample is many 23 companies registered on index IDX 80 with 115 data observations by using a purposive sampling method. Method of analysis data in this research is using regression panel data. Results of this research show that dividend policies measured by DPR, ESG score, enviromental and profitability has a significant effect on stock liquidity. And social score, governance and leverage has no significant effect on stock liquidity. The implications of research for companies can identify predictable financial and non-financial as factors affect the stock liquidity, The company needs to pay attention to profitability that can increase stock liquidity and also pay attention to dividend policy because dividends are able to attract investors so it can increase stock liquidity. Related to the environment score to be attention because of the information bad in this may impact on stock liquidity.